7 Three Dimensional Aspects of the Major Character in Oscar Wilde’s Vera - Mulyawan, I Wayan (Universitas Sanata Dharma, 2015)
Drama is a portrait of a real life situation and the theme of a drama is closely related to daily life conditions experienced by the character. A Character is defined as an entity, human or animal, that is created by the author. A good character should be natural and lifelike, especialy in physiological, psychological and sociological dimensions known as three dimensional aspect of a character. These dimensions are very interesting to discuss since they are very important to determine the qualities of the characters in a drama.Physiologically, Vera is described as a beautiful young lady with beautiful eyes. Sociologically, Vera is concluded as coming from an average family in Russia, living in a poor society, and living under tyranny. She has lived in an inn with her father before she saw her brother taken away to prison for seeking for liberty as a Nihilist. Psychologically, Vera is seen as a loving person though she does not put love as priority. She loves her country and her brother. She wants to revenge on the King for being a tyrant. She is a brave woman. It is seen from how she becomes a Nihilist to revenge for her brother and to end up the tyranny in her country.Keywords: physiological dimension, psychological dimension, and sociological dimension